Peranan Zakat Community Development Untuk Meningkatkan Pendapatan Mustahik Di Badan Amil Zakat Nasional Kabupaten Bondowoso - Zakina Rulinda Hijjas; Moehammad Fathorrazi; Anifatul Hanim (IJABAH, 2024)
This research has a purpose to analyze the role of the Zakat Community Development program conducted by BAZNAS towards the increase in mustahik income. ProgramZakat Community Development in the form of forming livestock groups with funds coming from Zakat, Infaq and alms from muzakki. This research data comes from primary data obtained through interviews and observations with BAZNAS administrators and mustahik while secondary data comes from documents, books and journals that are in accordance with the research. The methodology used in this research uses a qualitative method with a case study approach. The results of this research show that there are two livestock groups formed by BAZNAS, namely goats and rabbits. All needs for forming a livestock group come from zakat funds. These two livestock groups are managed by mustahik who are selected to become members. The livestock group was given assistance in the form of providing livestock, building cages and assistance by BAZNAS in collaboration with Jember University, Bondowoso Campus and the Regional Government. With the existence of a livestock group, mustahik have the opportunity to become a farmer and can increase their income and fulfill their living needs.